Analysis of Determinants of Risk Factors for Hepatitis B Incidence in Pregnant Women in Makassar City - Kartini; Muharti Syamsul (Science Midwifery, 2022)
Hepatitis B (HBV) infection in pregnant women has become a global concern because the most common transmission occurs worldwide, especially in endemic areas, namely mother-to-child transmission during the prepartum or perinatal period with the risk of contracting hepatitis B (HBV) infection. in children more than 90%. Quantitative research using observational analytic methods and case control study design was used to find risk factors. The sample size was obtained by means of "Total Sampling" for the case group as many as 45 respondents with a 1:1 ratio between the case and control groups. Data were processed and analyzed using chi-square test and logistic regression test. Statistical tests show that education level, parity, and sexual partners are risk factors for the incidence of hepatitis B in pregnant women. Meanwhile, age group and type of work are not risk factors for hepatitis B incidence in pregnant women. Education level, parity, and sexual partners are risk factors for hepatitis B incidence in pregnant women. Among all the risk factors found, sexual partners were the most at risk for the incidence of hepatitis B in pregnant women in Makassar City (p-value = 0.022; OR: 12.920; 95% CI: 1.440-115.894).